2019
DOI: 10.1111/cei.13379
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi cleaves galectin-3 N-terminal domain to suppress its innate microbicidal activity

Abstract: Summary Galectin-3 is the best-characterized member of galectins, an evolutionary conserved family of galactoside-binding proteins that play central roles in infection and immunity, regulating inflammation, cell migration and cell apoptosis. Differentially expressed by cells and tissues with immune privilege, they bind not only to host ligands, but also to glycans expressed by pathogens. In this regard, we have previously shown that human galectin-3 recognizes several genetic lineages of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…To neutralize the microbicidal properties of galectin-3, protozoan parasites Trypanosoma cruzi and Leishmania major have developed molecular mechanisms to proteolytically cleave galecin-3 at its N terminus. The cleaved galectin-3 retained the carbohydrate-binding capacity but failed to induce the immune response ( 135 , 136 ). In a recent report, Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…To neutralize the microbicidal properties of galectin-3, protozoan parasites Trypanosoma cruzi and Leishmania major have developed molecular mechanisms to proteolytically cleave galecin-3 at its N terminus. The cleaved galectin-3 retained the carbohydrate-binding capacity but failed to induce the immune response ( 135 , 136 ). In a recent report, Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon raised the question of possible causes and mechanisms through which T. cruzi affects lectin structure. Pineda et al (2020) demonstrated that parasite death induced by long-term interactions between galectin-3 and T. cruzi is avoided by cleavage of the lectin N -terminal domain. Through this mechanism, the parasite likely counteracts galectin-3-driven immunity and host microbicidal activity, highlighting a possible strategy developed by parasites to survive inside mammalian hosts ( Pineda et al, 2020 ).…”
Section: Galectin-3 and Trypanosoma Cruzi Infectionmentioning
confidence: 99%
“…Além disso, Gal-3 reconhece o parasito T. cruzi e dessa forma proporciona a morte do parasito. Essa molécula aparenta ter tanta importância no controle de T. cruzi que o próprio parasito, para evadir dos mecanismos imunológicos desencadeados por Gal-3 durante a infecção, altera a estrutura molecular da galectina, anulando assim os mecanismos de sinalização associados à imunidade inata que são desencadeados por esta leucina (PINEDA et al, 2015;PINEDA et al, 2020).…”
Section: Discussionunclassified